Hubungan Antara Kesiapan Belajar Dengan Prestasi Belajar Kimia Siswa Kelas XI SMAN 1 Wawo - Rahman, Muhammad Auliya; Siahaan, Jeckson; Haris, Mukhtar (FKIP University of Mataram, 2024)
This research purpose is to analyze relation between learning readiness and chemistry learning achievement in class XI MIA SMAN 1 Wawo, academic year 2022/2023. This research is quantitative descriptive. The data collection method uses student learning readiness questionnaire and documentation to obtain data on student chemistry learning achievement. The data analysis method used is inferential statistical analysis. The data processing method with parametric statistics uses the Product Moment Correlation formula. Presentation of data in the form of a frequency distribution table and group explanations through the highest score, lowest score, mean, median, mode, and standard deviation. The result of this study indicates that there is a significant relation between student learning readiness and chemistry learning achievement in class XI MIA SMAN 1 Wawo in the 2022/2023 academic year. This is shown by rcount (0.878) > rtable (0.254) and tcount (13.971) > ttable (2.021) at an error level of 5% and the contribution of learning readiness of 77.08% to learning achievement.